2006
DOI: 10.1086/507629
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Ionization Equilibrium for Optically Thin Plasmas. I. Updated Recombination Rate Coefficients for Bare through Sodium‐like Ions

Abstract: Reliably interpreting spectra from electron-ionized cosmic plasmas requires accurate ionization balance calculations for the plasma in question. However, much of the atomic data needed for these calculations have not been generated using modern theoretical methods and are often highly suspect. This translates directly into the reliability of the collisional ionization equilibrium (CIE) calculations. We make use of state-of-the-art calculations of dielectronic recombination (DR) rate coefficients for the hydrog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
189
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(194 citation statements)
references
References 58 publications
4
189
1
Order By: Relevance
“…They have found that for some ions the uncertainties in different calculations can be as large as a factor of 2−5. More recently, Bryans et al (2006) used updates to archived DR and RR data to find differences in peak fractional abundances of up to 60% compared to the commonly used data. Because of these uncertainties in low-temperature plasma rates, the relative elemental abundance inferred from the solar and stellar upper atmosphere, needed for modelling the astrophysical plasmas is A&A 557, A2 (2013) affected to a large extent (Chen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They have found that for some ions the uncertainties in different calculations can be as large as a factor of 2−5. More recently, Bryans et al (2006) used updates to archived DR and RR data to find differences in peak fractional abundances of up to 60% compared to the commonly used data. Because of these uncertainties in low-temperature plasma rates, the relative elemental abundance inferred from the solar and stellar upper atmosphere, needed for modelling the astrophysical plasmas is A&A 557, A2 (2013) affected to a large extent (Chen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…DR is a strong recombination channel at plasma temperatures where highly charged ions are common. In the calculation of fractional abundances of various charge states the results depend crucially on the atomic data used as input in the calculations (Bryans et al 2006). Sulfur and argon are astrophysically abundant elements (Anders & Grevesse 1989), accurate DR rate coefficients for their ions are thus important for the diagnostics and modeling of astrophysical plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, for open L and M shell ions the discrepancies between the results of state-of-the-art calculations amount to ∼35% (Bryans et al 2006). For DR resonances below 1−3 eV energy, the uncertainties are much higher, due to the inability of modern theory to accurately predict resonance positions, widths and strengths.…”
Section: Introductionmentioning
confidence: 99%
“…strath.ac.uk/tamoc/DR/. The total DR recombination rate is now substantially higher at temperatures below the ionization peak with the result that the gas tends to be more neutral (Bryans et al 2006(Bryans et al , 2009.…”
mentioning
confidence: 99%